Association of JAG1 gene polymorphism with systemic blood pressure in patients with obstructive sleep apnea: a prospective cohort study - Paraničová, Ivana (Croat Med J, 2019)
AIM: To assess the effects of single nucleotide polymorphisms (SNPs) on blood pressure control in patients with obstructive sleep apnea (OSA). METHODS: This prospective observational cohort study, conducted between 2004 and 2014, examined the associations of SNPs of JAG1, GUCY1A3-GUCY1B3, SH2B3, and NPR3-C5orf23 genes with systolic and diastolic blood pressure (SBP, DBP) in 1179 adults evaluated for OSA with overnight polysomnography. Genotyping was performed by unlabeled probe melting analysis. RESULTS: The patients were predominantly male (69.6%, mean age 52 ± 11 years, apnea-hypopnea index 34 ± 31 episodes/h). Only JAG1 genotype was associated with SBP and DBP: compared with AA homozygotes, G allele carriers (pooled GG and AG genotype) had significantly higher morning SBP (132 ± 19 vs 129 ± 18 mm Hg; P = 0.009) and morning and evening DBP (85 ± 11 vs 83 ± 10 mm Hg, P = 0.004; 86 ± 10 vs 84 ± 10 mm Hg, P = 0.012, respectively); the differences remained significant after the correction for multiple SNPs testing. In multivariate analyses, oxygen desaturation index and JAG1 genotype independently predicted morning SBP (P = 0.001, P = 0.003, respectively) and DBP (P < 0.001, P = 0.005, respectively), and evening SBP (P = 0.019, P = 0.048, respectively) and DBP (P = 0.018, P = 0.018, respectively). CONCLUSION: This is the first replication study of the SNPs recently linked to arterial hypertension in general population by genome-wide association studies. Our findings suggest that JAG1 genotype is related to blood pressure control in OSA: G allele was associated with higher morning and evening SBP and DBP.